Xeroderma Pigmentosum With Squamous Cell Carcinoma Of The Skin And Tip Of The Tongue - Kumar Parimalam; Manimegalai M; Jayaraman M (Wolters Kluwer Medknow Publications, 2000)
Xeroderma pigmentosum (XP) is a rare heterogeneous group of disorders with a high incidence of cutaneous malignancies. However, malignancies of the mucosa are rare. We report a case of XP in an eight-year-old boy who developed squamous cell carcinoma (SCC) of the tip of the tongue within a short period of two months. Biopsy from the lingual growth and a papule from the face showed SCC. We report this case for its rarity and for rapidity with the tongue cancer developed.